2012
DOI: 10.1097/wnn.0b013e318259594b
|View full text |Cite
|
Sign up to set email alerts
|

Normative Data for Healthy Middle-Aged and Elderly Performance on the Addenbrooke Cognitive Examination-Revised

Abstract: The performance of healthy middle-aged and elderly individuals on the ACE-R battery is strongly influenced by education and, to a lesser extent, by age. These findings are of special relevance in countries with populations that have marked heterogeneity in educational levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 31 publications
4
27
1
6
Order By: Relevance
“…Still, the education variable was shown to have a greater impact on scores in phonemic and semantic tests than age, suggesting that the number of years of education predicts better results, like the lower the age. These results are similar to other studies that did not fi nd association between gender and the number of words generated, but the infl uence of age and education (Amaral-Carvalho & Caramelli, 2012;Munro et al, 2012;Ryu et al, 2012;Snitz et al, 2009;Venegas & Mansur, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Still, the education variable was shown to have a greater impact on scores in phonemic and semantic tests than age, suggesting that the number of years of education predicts better results, like the lower the age. These results are similar to other studies that did not fi nd association between gender and the number of words generated, but the infl uence of age and education (Amaral-Carvalho & Caramelli, 2012;Munro et al, 2012;Ryu et al, 2012;Snitz et al, 2009;Venegas & Mansur, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Studies show that age is not a predictor of performance on tests of verbal fl uency (Brucki & Rocha, 2004;Venegas & Mansur, 2011). In contrast, Amaral-Carvalho and Caramelli (2012) found an association between age and performance of verbal fl uency tasks, as well as the results of other studies (Ryu et al, 2012;Silva et al, 2011;Snitz et al, 2009) corroborate the idea that the greater the age of the person, the smaller the words production of animals.…”
Section: Discussionmentioning
confidence: 63%
“…The scale was adapted and studied in the Brazilian population and showed that a cut-off score < 78 yielded high diagnostic accuracy for diagnosis of dementia 16,19 . That was a cut-off score far from what was observed in other studies conducted in different populations, in which the best cut-off scores were between 88 and 82.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that these scales can be useful and may be better than the MMSE to detect cognitive impairment in patients with PD 2,5,6,7,8,9,10,11,12,13,14,15 . In Brazil, the MoCA and ACE-R have been translated and adapted for clinical use, but their diagnostic validity in Brazilian clinical settings still remains uncertain 16,17,18,19 . Differences in formal education, prior exposure to formal testing environments, previous experience with or knowledge of specific test items (e.g., confrontational naming items), and other factors may limit the validity of a measure when applied cross-culturally.…”
mentioning
confidence: 99%
“…Haugurd et al (2010) afirmaram que a menor fluência verbal dos idosos pode estar relacionada ao declínio nas funções executivas, incluindo diminuição nas estratégias de pesquisa e recuperação eficiente das palavras, do que ao declínio no conhecimento semântico. O efeito da idade nas provas de fluência verbal semântica na população brasileira sadia foi analisado por Brucki et al (1997), Brucki, Rocha (2004), Steiner et al (2008), Fichman et al (2009), Amaral-Carvalho, Caramelli (2012 e Soares et al (2012). Os autores constataram que tanto a idade quanto a escolaridade influenciaram os resultados.…”
Section: Envelhecimento E Discursounclassified